Vliv uvolňování zinku při slinování na permeabilitu/indukčnost feritové keramiky - Kvapilová, Vendula (Vysoké učení technické v Brně. Fakulta chemická, 2021)
Diplomová práce je zaměřena na zkoumání vlivu uvolňování zinku při slinování feritů na permeabilitu/indukčnost feritové keramiky. Teoretická část pojednává o postavení feritů mezi ostatními keramickými materiály. Jsou zde popsány základní charakteristické vlastnosti feritů, jejich krystalová struktura a nakonec problémy, které se bezprostředně pojí s jejich výrobou a které zásadně ovlivňují magnetické vlastnosti feritů. Ve druhé části práce byl u připravených testovacích těles z průmyslových surovinových směsí zkoumán vliv teploty a času slinování a polohy jader v peci při výpalu na ztrátu zinku ze vzorku a následně na elektromagnetické vlastnosti. Jedná se o prvotní experimenty, na které bude navazovat další výzkum, jehož snahou bude odstranění problému ztráty zinku při výrobě Mn-Zn feritů.

The diploma thesis is focused on the investigation of the effect of zinc release during ferritic sintering on the permeability/inductance of ferrite ceramics. The theoretical part deals with the position of ferrites among other ceramic materials. It describes the basic characteristics of ferrites, their crystal structure and finally the problems that are directly related to their production and which fundamentally affect the magnetic properties of ferrites. In the second part of the work, the influence of the temperature and time of sintering and the position of the cores in the furnace during firing on the loss of zinc from the sample and subsequently on the electromagnetic properties of the prepared test specimens from industrial raw material mixtures was investigated. These are initial experiments, which will be followed by further research aimed at eliminating the problem of zinc loss in the production of Mn-Zn ferrites.
Influence of zinc loss during the sintering on permeability/inductance of ferrite ceramics
Keywords: Ferit; zinek; slinování; vypařování zinku; permeabilita; Ferrite; zinc; sintering; zinc evaporation; permeability